Երկրաշարժերի ապահովագրության համակարգի կատարելագործման հիմնախնդիրները ՀՀ-ում (ճապոնիայի օրինակով) - Հարությունյան, Գայանե (Քոփի Փրինթ)
For the normal functioning of each society, it is necessary to develop a proper policy and strategy that will allow both timely prevention of losses that have occurred and compensation of them. Among such damages, one can distinguish damages caused by natural disasters (earthquake, flood, hurricane, landslide, etc.). Risk insurance, in which the State has its share, is considered to be one of the effective mechanisms for compensation of losses. From the point of view of implementing an effective system, it is important to study the systems of countries with experience in this area. The article presents the features of the earthquake insurance system in Japan, compared with a similar system operating in Armenia. As a result, a number of suggestions were made.
Keywords: Տնտեսագիտություն